The philosophical impact of european fiction on contemporary views of war and peace - Kobzei, Natalia; Ieliseienko, Anna; Pysarska, Nataliia; Diachuk, Liudmyla; Rak, Marta (Universidade Católica de Petrópolis, 2024)
The aim of the study is to analyse the influence of fiction on the perception of war and peace in the modern world. The research employed the methods of linguistic analysis, factor analysis, and questionnaire survey. The following statistical methods were used: Mann–Whitney U test, Pearson correlation coefficient, correlation analysis. The reliability of the instruments was tested using Cronbach’s alpha coefficient. The results of the study showed that fiction has a significant impact on the perception of war and peace in the modern world. The determining role of literature in the formation of worldview consciousness of readers was also established, which emphasizes its philosophical significance. It was also established that the variety of literary works allows for the presentation of different points of view on war and peace, which contributes to the formation of different ideas and views on these topics. All this emphasizes the importance of fiction as a means of promoting awareness and cultural understanding of modern conflicts and ways to peace. Fiction plays an important role in shaping ideas about war and peace in the modern world. It conveys realistic images of conflicts and peace negotiations, but also promotes the development of empathy and understanding of different perspectives on these issues. Further research could include a more in-depth analysis of the influence of specific literary works on perceptions of war and peace, taking into account various aspects such as cultural characteristics, social context, and individual characteristics of readers.
Keywords: fiction; the concept of peace; the concept of war; memory; reconciliation; formation of worldview; ethical influence